MATEH EMAS, IDOP ASA': INTERPRETING THE RISK SOCIETY OF CROCK MINERS IN WEST KALIMANTAN, INDONESIA - Rafi Rendian Sulaksono (Jurnal Mahasiswa Antropologi dan Sosiologi Indonesia (JuMASI), 2026)
This study examines the practice of illegal mining (PETI) in Batangk Atas Sub-District, Ketapang Regency, West Kalimantan Province, as a social phenomenon emerging within conditions of economic and ecological uncertainty. It aims to analyze the formation and persistence of PETI as a livelihood strategy for local communities, as well as how miners perceive and manage risks to their bodies and the environment. A qualitative ethnographic approach was employed, with data collected through literature review, participant observation, semi-structured interviews, focus group discussions, and documentation during two months of fieldwork (August-September 2025) conducted in collaboration with Gaia Indonesia as part of the Socio-Economic Study Project. The study involved seven informants three key informants and four supporting informants selected through purposive and snowball sampling. Data were analyzed using an interactive qualitative model comprising data reduction, data display, and conclusion drawing/verification. The analysis is grounded in the risk society framework to examine the relationship between risk, modernity, and informal economic practices. The findings indicate that PETI cannot be understood merely as an illegal activity, but rather as a historically institutionalized practice that generates enduring structural risksincluding occupational accidents, mercury exposure, and environmental degradationwhich local communities address through adaptive strategies to sustain their livelihoods.